INFLUENCE DIFFERENCE HEALTHY EDUCATION SIMULATION METHOD AND SIMULATION WITH POSTER METHOD ABOUT BREASTFEEDING TECHNIQUE TO MOTHER WET NURSE KNOWLEDGE AT SAJEN VILLAGE KECAMATAN TRUCUK KABUPATEN KLATEN - Eni Purwanti; Zaenal Arifin; Dwi Sri Handayani (STIKES DUTAGAMA KLATEN, 2012)
Background: The breastfeeding technique is one of influence factor mother’s milk product if breastfeeding technicque not right cause nipple rub until make mother’s unwilling breastfeeding and the infants suckle on the breast rare. If the infants suckle on the breast rare it will not good result because the infant inhaled or suck very influence enough mother’s milk product stimulus furthermore. Objective: This reaseach was aim to find the influence difference helth education simulation method proportionate simulation with poster metode about breastfeeding technique to mother wet nurse knowledge at Sajen village. Method: This was a quasi ekperiment with quantitative non equivalent control group design. The population in the reaseach was mother’ wet nurse at the Sajen village, this sample was taken with purposive sampling, with the sample of 30 respondents be based on inclusive and eksclusive criteri. The measurement of knowledge mothers wet nurse use questioner. Data processing used SPSS 16.0 program with one way anova analyze. Result: The result this reaseach showed that discover influence different between health education with simulation method and simulation with poster about the right breastfeeding technique to mother wet nurse knowledge ( Fh 5,912;Ft 3,35; p= 0,007; tukey Simulation 2,50, simulation with poster 2,70 mean difference =0,20) Conclution: Healthy education simulation with poster method about the right breastfeeding technique more influence to mother wet nurse knowledge proportion simulation method.